IMPLIKASI PENOLAKAN LAPORAN KETERANGAN PERTANGGUNG- JAWABAN KEPALA DAERAH DALAM PERSPEKTIF HUKUM TATA NEGARA - Komari Komari (Jurnal Dinamika Hukum, 2009)
The Format of Indonesia Local Government that change with implementation Law Number 32 year 2004 concerning Local Government replaces Law Number 22 year 1999 concerning Local Government, the one of consequence change that is about responsibility the leader of local government. In implementation Law Number 22 year 1999 concerning Local Government, the leader of local government is responsible to DPRD as a local parlement with mechanism Responsible Report. DPRD as a local government have a authority to give and punish if a Responsible Report accepted or rejected with implicated the leader of local government can be impeacthment. The important point in implementation in Law Number 32 year 2004 concerning Local Government, with the simetris position like a partenership between leader of local government and DPRD as a local parlement is nothing implication of law with rejected to Progres Report the Leader of Local Government, as a like impeacthment, to claim in court or punish can not able to be a candidat in leader of local government in the next election.  Kata kunci:  Laporan Pertanggungjawaban, Kepala Daerah, Pemerintahan Daerah